2005
DOI: 10.1074/jbc.m406987200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Muscarinic Receptor-linked Phospholipase D Activation by Association with Tubulin

Abstract: Mammalian phospholipase D (PLD) is considered a key enzyme in the transmission signals from various receptors including muscarinic receptors. PLD activation is a rapid and transient process, but a negative regulator has not been found that inhibits signal-dependent PLD activation. Here, for the first time, we report that tubulin binding to PLD 2 is an inhibition mechanism for muscarinic receptor-linked PLD 2 activation. Tubulin was identified in an immunoprecipitated PLD 2 complex from COS-7 cells by peptide m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 63 publications
(58 reference statements)
3
32
0
Order By: Relevance
“…Previous studies have shown that PLD activity can be regulated by various protein kinases such as PKC, protein-tyrosine kinases, and the MAP kinase family as well as the small G proteins from the ARF, Rho, and Ras families (38,39). Furthermore, the activity of PLD has been shown to be regulated through interactions with various cytoskeletal proteins such as tubulin, actin, and ␣-actinin (40)(41)(42). For example, Park et al (41) demonstrated that PLD can bind to ␣-actinin and that this interaction inhibits the activity of PLD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that PLD activity can be regulated by various protein kinases such as PKC, protein-tyrosine kinases, and the MAP kinase family as well as the small G proteins from the ARF, Rho, and Ras families (38,39). Furthermore, the activity of PLD has been shown to be regulated through interactions with various cytoskeletal proteins such as tubulin, actin, and ␣-actinin (40)(41)(42). For example, Park et al (41) demonstrated that PLD can bind to ␣-actinin and that this interaction inhibits the activity of PLD.…”
Section: Discussionmentioning
confidence: 99%
“…COS-7 cells were maintained in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% (vol/vol) fetal bovine serum at 37°C in a humidified, CO 2 -controlled (5%) incubator. For transfection and the transient expression of proteins, cells were transfected using Lipofectamine, as described previously (4). The following plasmids were used to induce overexpression: pcDNA3.1-HA-PKC␣, pcDNA3.1-HA-PKC␦, pcDNA3.1-HA-PKCε, pcDNA3.1-HA-DN-PKC␣, pcDNA3.1-HA-DN-PKC␦, pcDNA3.1-HA-DN-PKCε, pEGFP-C1-PLD2, and pcDNA3.1-FLAG-V12-Rac1.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, little is known about the regulation of PLD2 although its activity is dependent upon PtdIns(4,5)P 2 and it has been hypothesised that availability of this lipid may be a major factor in its regulation (Divecha et al, 2000). Furthermore, in contrast to PLD1 which also requires PtdIns(4,5)P 2 for activation, PLD2 has been shown to have high basal activity in the presence of PtdIns(4,5)P 2 and may therefore be subject to negative regulation through direct protein interaction as has been demonstrated through interaction with proteins such as actin, α-actinin, α-synuclein and tubulin (Lee et al, 2001;Park et al, 2000;Payton et al, 2004;Chae et al, 2005).…”
mentioning
confidence: 99%